Association between treatment failure in patients with early syphilis and penicillin resistance-related gene mutations of Treponema pallidum: Protocol for a multicentre nested case–control study - Mi, Hong-Fei; Shen, Xu; Chen, Xiao-Qing; Zhang, Xiao-Luo; Ke, Wu-Jian; Xiao, Yao (Frontiers in Medicine, 2023)
Background: The widespread occurrence of syphilis remains a global public health problem. Although penicillin has been recommended as the first-line therapy for syphilis for more than 70 years, treatment failure occurs in 10%-20% of patients with early syphilis. Recent studies have reported varied single-nucleotide polymorphisms (SNPs) of T. pallidum related to penicillin resistance. The clinical relevance of these SNPs to treatment failure in patients with early syphilis is unresolved. In this work, a protocol is developed to evaluate the association between treatment failure in patients with early syphilis and penicillin resistance-related gene mutations of T. pallidum. Methods: A multicentre nested case‒control study is designed, and patients who are diagnosed with early syphilis and treated with penicillin will be recruited for the study cohort. Before the first treatment, baseline information and biological specimens will be collected from the subjects, and serological tests for syphilis will be performed. Each participant will be followed up at 1, 3, 6, 9, and 12 months after the first treatment, and the clinical manifestations and serum nontreponemal test titres will be evaluated at each follow-up. Patients who will fail treatment are defined as cases, and those who will respond to treatment are defined as controls. Tests for SNPs related to penicillin-binding proteins and Tp47 will be performed in these cases and controls. Survival analysis is used performed to identify gene mutations of T. pallidum related to penicillin resistance and their combinations associated with treatment failure. Discussion: This protocol provides a practical clinical study design that illustrates the role of gene mutations of T. pallidum related to penicillin resistance in the treatment outcome of patients with early syphilis.